Benzalkonium chloride and cetylpyridinium chloride induce apoptosis in human lung epithelial cells and alter surface activity of pulmonary surfactant monolayers. (1st February 2020) - Kanno, Sanae; Hirano, Seishiro; Kato, Hideaki; Fukuta, Mamiko; Mukai, Toshiji; Aoki, Yasuhiro
Abstract: Quaternary ammonium compounds (e.g., benzalkonium chloride (BAC) and cetylpyridinium chloride (CPC)) constitute a group of cationic surfactants are widely used for personal hygiene and medical care despite the potential pulmonary toxicity. To examine whether BAC and CPC aerosols deposited in the alveolar region alter pulmonary function, we studied the effects on pulmonary surfactant using two-step in vitro models; cytotoxicity using A549 alveolar epithelial cell and changes in surface activity of the pulmonary surfactant monolayer using both Surfacten® and 1, 2-dipalmitoyl- sn -glycero-3-phosphocholine (DPPC). Cell viability was decreased with BAC and CPC dose-dependently. A comparison of cytotoxicity among BAC homologues with different length of alkyl chain showed that C16 -BAC, which has the longest alkyl chain, was more cytotoxic than C12 - or C14 -BAC. Caspase-3/7 activity and cleaved form of caspase-3 and PARP were increased in BAC- and CPC-exposed cells. The elevated caspase-3/7 activity and their cleaved active forms were abolished by caspase-3-inhibitor. Furthermore, we examined the features of the surface pressure/trough area (π-A) isotherm by the Langmuir-Wilhelmy method and atomic force microscopy (AFM) images of lipid monolayers on a subphase containing BAC, CPC, or pyridinium chloride (PC, as a control). The π-A isotherms showed that addition of BAC or CPC yielded dose-dependent increases in surface pressure without compression, indicating that BAC and CPC expand the isotherm to larger areas at lower pressure. The collapse pressure diminished with increasing concentration of CPC. Topographic images indicated that BAC and CPC resulted in smaller condensed lipid domains compared to the control. Conversely, PC without hydrocarbon tail group, showed no cytotoxicity and did not change the isotherms and AFM images. These results indicate that BAC and CPC cause cell death via caspase-3-dependent apoptotic pathway in A549 cells and alter the alveolar surfactant activity. These effects can be attributed to the long alkyl chain of BAC and CPC. Graphical abstract: Image 1 Highlights: Deposition of disinfectant on the lung surface alter the alveolar surface activity. Disinfectants change the shape of π/A isotherm in pulmonary surfactant monolayer. A hydrophobic tail hydrocarbon group of disinfectant interacts with surfactant lipid. Disinfectants result in smaller condensed lipid domain of pulmonary monolayer. Disinfectants cause cell death via caspase-3-dependent apoptotic pathway.